Being the boss : the 3 imperatives for becoming a great leader - Hill, Linda A. 1956- (Harvard Business Review Press, 2011)
You never dreamed being the boss would be so hard. You're caught in a web of conflicting expectations from subordinates, your supervisor, peers, and customers. You're not alone. As Linda Hill and Kent Lineback reveal in "Being the Boss", becoming an effective manager is a painful, difficult journey. It's trial and error, endless effort, and slowly acquired personal insight. Many managers never complete the journey. At best, they just learn to get by. At worst, they become terrible bosses. This new book explains how to avoid that fate, by mastering three imperatives: · Manage yourself: Learn that management isn't about getting things done yourself. It's about accomplishing things through others -- Manage a network: Understand how power and influence work in your organization and build a network of mutually beneficial relationships to navigate your company's complex political environment -- Manage a team: Forge a high-performing "we" out of all the "I"s who report to you. Packed with stories and practical guidance, "Being the Boss" is a guide for not only first-time managers but all managers seeking to master the most daunting challenges of leadership.